Physical activities in the wheelchair and out an illustrated guide to personalizing participation - Davis, E. Ann 1949- (Human Kinetics, 2012)
"Physical Activities In the Wheelchair and Out is an illustrated book of games, skills, and activities for individuals with severe or multiple disabilities who may or may not use wheelchairs. The book can also be used with students who have normal developmental skills. By suggesting ways that many familiar skills, games, and activities might be performed, Physical Activities In the Wheelchair and Out offers opportunities for those with mobility challenges and disabilities to participate on their own terms."--Publisher's website.